2016
DOI: 10.5194/hess-20-3651-2016
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of climate and hydrological uncertainties in transient low-flow projections

Abstract: International audienceThis paper proposes a methodology for estimating the transient probability distribution of yearly hydrological variables conditional to an ensemble of projections built from multiple general circulation models (GCMs), multiple statistical downscaling methods (SDMs), and multiple hydrological models (HMs). The methodology is based on the quasi-ergodic analysis of variance (QE-ANOVA) framework that allows quantifying the contributions of the different sources of total uncertainty, by critic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 86 publications
(123 reference statements)
2
44
0
Order By: Relevance
“…Several other studies also identified snow processes as critical in hydrologic projections (e.g. Dobler et al, 2012;Vidal et al, 2016). These results provide a strong motivation to carefully test the snow conceptualization in hydrologic models before applying them in climate change impact studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several other studies also identified snow processes as critical in hydrologic projections (e.g. Dobler et al, 2012;Vidal et al, 2016). These results provide a strong motivation to carefully test the snow conceptualization in hydrologic models before applying them in climate change impact studies.…”
Section: Discussionmentioning
confidence: 66%
“…The representation of underlying (physical) principles of hydrological processes in the hydrologic model can thus have a profound effect on the results and conclusion of a study. Although uncertainty in hydrologic projections has already been discussed and investigated in the literature, studies usually focus on one source of uncertainty (Gutmann et al, 2014) or a limited number of catchments (Vidal et al, 2016;Addor et al, 2014;Dobler et al, 2012). Here, we investigate three sources of uncertainty (GCM forcing, hydrologic parameters, hydrologic model structure) in hydrologic projections for 605 basins throughout the contiguous US over a wide range of climates, in order to reveal spatial patterns in uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Streamflow sequences were then used as input into water supply systems models to assess performance over time. Hydrologic model error is an additional source of uncertainty, with possible errors associated with the hydrologic model parameters, model structure, and prediction errors [ Steinschneider et al , ; Renard et al , ; Khan and Coulibaly , ; Hingray and Saïd , ; Vidal et al , ]. However, we do not address hydrologic model uncertainty because it is not expected to be significant in this case per conclusions of several earlier studies, particularly for nonextreme runoff quantiles [ Steinschneider et al , ; Dobler et al , ; Bosshard et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…However, dispersion within hydrological models is perceptible on the graphs, e.g., the CLSM model projects more substantial decrease in summer flows than the other models. This scattering stems from the difference in the evapotranspiration and snow pack components of the selected hydrological models [18]. The sign and the magnitude of the seasonal changes depend on the current river flow regime.…”
Section: Water Management and Regulatory Frameworkmentioning
confidence: 99%